2018
DOI: 10.1093/heapol/czx027
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to ranking countries for the allocation of development assistance for health: choices, indicators and implications

Abstract: The distributions of income and health within and across countries are changing. This challenges the way donors allocate development assistance for health (DAH) and particularly the role of gross national income per capita (GNIpc) in classifying countries to determine whether countries are eligible to receive assistance and how much they receive. Informed by a literature review and stakeholder consultations and interviews, we developed a stepwise approach to the design and assessment of country classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A recent study [23] found that donors considered a number of factors in the allocation and distribution of their aid to a country, including the health needs, domestic capacity, expected impact, and the cross-cutting concern for equity, in the case of development assistance for health. However, the relative importance of each of these factors varied across donors as well as the indicators used to operationalize each of the factors, a similar situation observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [23] found that donors considered a number of factors in the allocation and distribution of their aid to a country, including the health needs, domestic capacity, expected impact, and the cross-cutting concern for equity, in the case of development assistance for health. However, the relative importance of each of these factors varied across donors as well as the indicators used to operationalize each of the factors, a similar situation observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A similar misalignment occurs with total DAMH (Gilbert et al ., 2015; Charlson et al ., 2017) and DAH (Dieleman et al ., 2014). While allocation of development assistance is determined by a variety of factors beyond needs, including policy environment and donor interests (Hoeffler and Outram, 2011), stakeholders recognise health needs as of primary concern (Ottersen et al ., 2018). Similarly, factors beyond needs drive philanthropic giving, including solicitation, cost-benefit, altruism, reputation, psychological benefits, values and efficacy (Bekkers and Wiepking, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While donors, including Japan, have their own methodologies for deciding how to distribute DAH, the criteria for assessing equity in the distribution of their DAH can include national income (an indicator of economic needs) and disease burden (an indicator of health needs). 21 , 22 Figure 3 shows that the relationship between Japan's DAH per capita and GNI per capita in 2018 is weak. Although the general tendency is for higher GNI per capita to be associated with lower DAH per capita, there is wide variation in the amount of DAH received even among countries with similar levels of GNI.…”
Section: Methodsmentioning
confidence: 99%
“…Donors are likely to focus on the expected impact of DAH in terms of changes in health or determinants of health (including health service coverage), the ability (beyond financial factors) of countries to implement and expand services, and the fair distribution of resources and services. 21 In addition, DAH allocations from donor countries may be guided by a number of additional factors, such as historical diplomatic relations, geographic proximity, strategic political interests, and especially in the case of bilateral aid, trade-related considerations. 24,25 A fundamental challenge for donors, including Japan, is critically reviewing each country's own criteria and rationale for DAH allocation.…”
Section: How To Focus Dah For Equitable Health Gainsmentioning
confidence: 99%